164 LUNG PARENCHYMAL DEVELOPMENT IS IMPROVED IN PRETERM LAMBS MANAGED BY NASAL CONTINUOUS POSITIVE AIRWAY PRESSURE FOR 21 DAYS. (1st January 2006) - Albertine, K. H.; Null, D. M.; Dahl, M. J.; Shumway, A.; Lane, R. H.
Abstract : Background: In the premature infant, volume trauma contributes to the pathogenesis of chronic lung disease, which is characterized by an arrest of alveolar secondary septation. Similarly, conventional mechanical ventilation (CV) in the preterm lamb inhibits secondary septation. Nasal continuous positive airway pressure (nCPAP) is being used more frequently because the incidence of chronic lung disease is lower than with CV, and a recent study in preterm baboons demonstrated improved septation. We have used nCPAP to manage preterm lambs for up to 3 days, which is associated with better gas exchange and lung secondary septation than CV. Whether those benefits persist in preterm lambs managed for 21 days has not been determined. Objective: We hypothesized that management of preterm lambs for 21 days, using nCPAP, will be associated with improved gas exchange and alveolar secondary septation compared to CV. Methods: Preterm lambs were delivered at 132 days of gestation. All lambs were treated with antenatal steroids and postnatal surfactant. The lambs were managed with nCPAP ( n = 4) or CV ( n = 3) for 21 days. An oscillatory circuit (Bird; Percussionaire) was used to deliver CPAP to the nose. Target PaO2 was 60-70 mm Hg; target PaCO2 was 50-60 mm Hg. Ventilator and gas exchange parameters were assessed and lung tissue was analyzed morphologically. Results: For the target PaO2 (60-70 mm Hg), the fractional inspired O2 was significantly less in the nCPAP lambs (30 ± 8 mm Hg; mean ± SD) vs the CV lambs (54 ± 14 mm Hg) at weeks 1, 2, and 3 of life. For the target PaCO2 (50-60 mm Hg), peak inspiratory pressure, positive end-expiratory pressure, and mean airway pressure also were significantly less in the nCPAP lambs (19 ± 5, 5 ± 3, 4 ± 2, cmH2 O, respectively) vs the CV lambs (26 ± 8, 9 ± 3, 6 ± 2, cmH2 O) at weeks 1, 2, and 3 of life. Alveolar secondary septation was significantly greater in the nCPAP lambs (volume density 22 ± 4%) vs CV (5 ± 3%). Conclusion: Management of preterm lambs for 21 days, using nCPAP, resulted in improved gas exchange and alveolar secondary septation. Supported by CHRC, HL62875, HL56401, T35 HL07744.